Analisa Perbandingan Metode Lifting Hammer Menggunakan Crane dan Frame Portal untuk Uji PDA Pada Tiang Bore Pile Berdasarkan Analisa Mutu, Waktu dan Biaya - Ali Zainal Abidin Isa Alhabsyi; Ifthar Ramadhana W; Hendrata Wibisana; Karina Meilawati Eka Putri (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
The foundation is an important part of building construction, acting as a support for the building and transferring loads evenly from the upper structure to the ground. In construction projects, one of the most important activities is to test the bearing capacity of bore piles using the Pile Driving Analyser (PDA) method. The purpose of this test is to ensure that the capacity of the bored pile can meet the structural requirements of the toll road, particularly in the face of significant vertical and lateral loads. Improving the efficiency of the PDA (Pile Driving Analyzer) testing method is an important challenge in the foundation of bored piles in infrastructure projects. This study discusses the analysis of the use of the Frame Portal PDA as an alternative to the crane hammer method. The analysis includes quality, time and cost aspects on the Toll project. The results show that the PDA Portal Frame method is more efficient with a cost saving of Rp109,010,524.00 and a reduction in implementation time for 2 days of test points compared to the crane method. In addition, the PDA Portal Frame structure has a maximum deformation of 0.030 mm, which is within safe limits according to SNI 2847-2019.